The Role of Principal Leadership in Improving Educational Quality at MTs Manbatul Fikri Curugrendeng: (Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan di MTs Manbatul Fikri Curugrendeng) - Agus; Alwi Sofwan Al-giffari; Debi Putri Serena; Afif Nurseha (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This study aims to investigate the strategic role of principal leadership in enhancing educational quality at MTs Manbatul Fikri Curugrendeng. A qualitative methodology was employed, utilizing semi-structured interviews and field observations with the school principal as the primary data collection techniques. Data were analyzed using a phenomenological approach to capture the essence of leadership experiences and practices. The findings demonstrate that the principal's leadership exerts a significant influence on the improvement of educational standards. Key factors contributing to this enhancement include the articulation of a robust vision and mission, systematic teacher professional development, fostering collaborative synergy, and implementing effective resource management. These elements constitute a comprehensive leadership framework essential for driving academic and institutional excellence in the Islamic school context.